2019
DOI: 10.1186/s13584-018-0271-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparity in Israel impacts long-term results after heart transplantation

Abstract: BackgroundEthnicity may affect graft longevity and recipient mortality after heart transplantation (HTx). We hypothesized that differences in ethnic origin between Arabs and Jews undergoing HTx in Israel may contribute to differences in long-term outcomes.MethodsThe study population comprised all 254 patients who underwent HTx between 1991 and 2017 in a tertiary medical center located in the center of Israel. Patients were categorized as either Jews (226 patients, 89%) or Arabs (28 patients, 11%). The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…In a previous study assessing the influence of Jewish and Arab ethnicity and HT outcomes, no differences were found in the rejection rates solely according to the patient's ethnic group, or in the time to first major rejection . However, in the present study, we demonstrated that donor‐recipient ethnic mismatch was associated with a higher rejection rate.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…In a previous study assessing the influence of Jewish and Arab ethnicity and HT outcomes, no differences were found in the rejection rates solely according to the patient's ethnic group, or in the time to first major rejection . However, in the present study, we demonstrated that donor‐recipient ethnic mismatch was associated with a higher rejection rate.…”
Section: Discussioncontrasting
confidence: 76%
“…The effect of donor‐recipient ethnic mismatching was already evident in the immediate post‐transplant period, with >8‐fold increased risk for PGD and >7‐fold increased risk for in‐hospital mortality. In a previous study, we showed that the ethnic origin of Arabs is associated with a significantly increased risk for CAV and mortality following HT . Based on these findings, our current study results have been adjusted to Arab ethnic origin.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations